1993
DOI: 10.1002/aja.1001970207
|View full text |Cite
|
Sign up to set email alerts
|

In situ hybridization studies suggest a role for the basic region‐leucine zipper protein hXBP‐1 in exocrine gland and skeletal development during mouse embryogenesis

Abstract: The spatial and temporal distribution of transcripts for the TREERE-binding basic region-leucine zipper protein hXBP-1 was determined by in situ hybridization. Analysis of embryos from day 10.5 to 18.5 pc revealed high level expression of hXBP-1 RNA in two developing organ systems: 1) in bone and cartilage cells of the developing skeleton and toothbuds, and 2) in exocrine glands including the pancreas and the submandibular and salivary glands. High level expression was also found in whisker follicles and in se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
59
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(59 citation statements)
references
References 40 publications
0
59
0
Order By: Relevance
“…62,63 XBP-1 mRNA is ubiquitous in adult tissues but preferentially expressed in the fetal exocrine glands, osteoblasts, chondroblasts and liver. 64 Like HAC1, newly synthesized XBP-1 transcript must be spliced by activated Ire1 to a mature, efficiently translated mRNA. 62,63 When activated by ER stress, Ire1 excises an intron from the immature XBP-1 transcript, resulting in the replacement of the C-terminal domain of the protein and the translational activation of the mRNA, analogous to the splicing of HAC1 mRNA.…”
Section: Esr In Mammalsmentioning
confidence: 99%
“…62,63 XBP-1 mRNA is ubiquitous in adult tissues but preferentially expressed in the fetal exocrine glands, osteoblasts, chondroblasts and liver. 64 Like HAC1, newly synthesized XBP-1 transcript must be spliced by activated Ire1 to a mature, efficiently translated mRNA. 62,63 When activated by ER stress, Ire1 excises an intron from the immature XBP-1 transcript, resulting in the replacement of the C-terminal domain of the protein and the translational activation of the mRNA, analogous to the splicing of HAC1 mRNA.…”
Section: Esr In Mammalsmentioning
confidence: 99%
“…Finally, there have been several studies that have shown an increased expression of c-fos in bone from patients with fibrous dysplasia, in which there is an overexpression or ectopic expression of bone formation (20). In a number of recent studies, members of the basic leucine zipper protein family, including c-fos (21,22), hXBP (23), and ATF2 (24) have been shown to be expressed selectively during normal skeletal tissue development. Finally, in recent studies, the ablation of one of these factors, ATF2, led to a defect in endochondral ossification, which has a similar histopathology to human hypochondroplasia (24).…”
Section: Pthmentioning
confidence: 99%
“…As a member of the ATF/CREB transcription factor family that activate promoters containing specific cyclic AMP responsive elements (CRE) (33), hXBP-1 regulates the expression of several tissue-specific genes, including tissue inhibitor of metalloproteinases, osteopontin and osteocalcin (34). Potentially downstream of NFκB activation in some cells (35), hXBP-1 is associated with increased proliferation and reduced apoptosis (16), which implies a survival function.…”
Section: Introductionmentioning
confidence: 99%